Grading of meningeal solitary fibrous tumors/hemangiopericytomas: analysis of the prognostic value of the Marseille Grading System in a cohort of 132 patients. (7th May 2018) - Macagno, Nicolas; Vogels, Rob; Appay, Romain; Colin, Carole; Mokhtari, Karima; ,; ,; Küsters, Benno; Wesseling, Pieter; Figarella‐Branger, Dominique; Flucke, Uta; Bouvier, Corinne
Abstract: The finding that meningeal solitary fibrous tumors (SFTs) and meningeal hemangiopericytomas (HPCs) are both characterized by NAB2‐STAT6 gene fusion has pushed their inclusion in the WHO 2016 Classification of tumors of the central nervous system (CNS) as different manifestations of the same entity. Given that the clinical behavior of the CNS SFT/HPC spectrum ranges from benign to malignant, it is presently unclear whether the grading criteria are still adequate. Here, we present the results of a study that analyzed the prognostic value of an updated version of the Marseille Grading System (MGS) in a retrospectively assembled cohort of 132 primary meningeal SFTs/HPCs with nuclear overexpression of STAT6. The median patient follow‐up was 64 months (range 4–274 months); 73 cases (55%) were MGS I, 50 cases (38%) MGS II and 9 cases (7%) were MGS III. Progression‐free survival (PFS) and disease‐specific survival (DSS) were investigated using univariate analysis: the prognostic factors for PFS included MGS, extent of surgery, radiotherapy, chemotherapy and mitotic activity ≥5/10 high‐power field (HPF). Moreover, MGS, radiotherapy, mitotic activity ≥5/10 HPF, and necrosis were the prognostic factors measured for DSS. In multivariate analysis, extent of surgery, mitotic activity ≥5/10 HPF, MGS I and MGS III were the independent prognostic factors measured for PFS while necrosis, MGS III and radiotherapy were the independent prognostic factors for DSS. In conclusion, our results show that assessing the malignancy risk of SFT/HPC should not rely on one single criterion like mitotic activity. Therefore, MGS is useful as it combines the value of different criteria. In particular, the combination of a high mitotic activity and necrosis (MGS III) indicates a particularly poor prognosis.